Perilaku Pengguna Jasa Karantina Pertanian dalam Mendukung Perlindungan Sumberdaya Alam Hayati - Ririn Setyowati; Akhmad Fauzi; Eko S. Pribadi; Hari Wijayanto (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
Agricultural quarantine is the forefront of Indonesia’s natural biodiversity and technical barrier in agricultural    commodities trade. This study aimed to analyze the user behavior of service users in utilizing agricultural quarantine services in relation to supporting the protection of natural resources biodiversity. This study used primary data, with purpossive random sampling as the sampling technique. Multiple regression analysis, Customer Satisfaction Index (CSI), and Structural Equation Modelling(SEM) were carried on this study. Through CSI calculation obtains the CSI value is 78.26% at satisfied range.The result of multiple re-gression analysis test indicated that emphaty, responsiveness, reliability, assurance, and tangible have    significant influence to service user satisfaction. Hypothesis testing using SEM so that it is known that the perception and service quality have significant influence on user behavior characterized by participation and compliance level. By knowing the level of participation and compli-ance of service users is useful in determining and formulating strategies to increase protection of natural resources biodiversity through quarantine action.